The beast : a Decker/Lazarus novel - Kellerman, Faye (Kellerman, Faye. Decker/Lazarus novel., 2013)
"Over the years, Peter Decker and Rina Lazarus have got through a lot together. They've faced more than their share of serial killers and psychopaths. But this time two very different cases may cause them to re-evaluate everything they hold dear. One case involves Gabe, the troubled boy they've taken into their home. The other is much stranger - a man is found dead in his apartment, apparently mauled by his pet tiger. There is more to each case than anyone expects. But will Decker's family distractions finally prove too much? And when the truth comes out, will Rina and Peter's family survive?"--